2021
DOI: 10.1016/j.xphs.2021.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Benzylpenicillin as an Internal Standard for Measurement of Piperacillin Bone Concentrations Via Microdialysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Only a few studies have previously investigated piperacillin bone concentrations, and no studies have evaluated intervertebral disc concentrations [ 29 , 30 , 31 ]. A recent piperacillin STI single dose (4/0.5 g) microdialysis porcine study found a notably longer mean f T > MIC (16 g/mL) of 255 min (57%) in tibial cancellous bone during a 480 min sampling period compared to the present of 82 min (25%) in vertebral cancellous bone (STI dosing in third dosing interval and 360 min sampling period).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies have previously investigated piperacillin bone concentrations, and no studies have evaluated intervertebral disc concentrations [ 29 , 30 , 31 ]. A recent piperacillin STI single dose (4/0.5 g) microdialysis porcine study found a notably longer mean f T > MIC (16 g/mL) of 255 min (57%) in tibial cancellous bone during a 480 min sampling period compared to the present of 82 min (25%) in vertebral cancellous bone (STI dosing in third dosing interval and 360 min sampling period).…”
Section: Discussionmentioning
confidence: 99%
“…A recent piperacillin STI single dose (4/0.5 g) microdialysis porcine study found a notably longer mean f T > MIC (16 g/mL) of 255 min (57%) in tibial cancellous bone during a 480 min sampling period compared to the present of 82 min (25%) in vertebral cancellous bone (STI dosing in third dosing interval and 360 min sampling period). This may be explained by discrepancies between dosing interval, anatomical location, and/or bone structure, exemplifying that bone is a heterogeneous compartment [ 29 ]. Previous bone specimen studies from human jaw, hip, and femoral bone, have reported piperacillin cancellous bone tissue penetration in the range of 0.15–0.23, which is in line with the penetration to vertebral cancellous bone in Group STI (0.21) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microdialysis is a catheter-based method for continuous sampling of the free unbound and active fraction of antibiotics in the interstitial space of the tissue of interest [ 43 , 44 , 45 ]. A semipermeable membrane at the tip of the catheter allows solutes to diffuse along the concentration gradient, but without achieving equilibrium, as the microdialysis catheter is constantly perfused.…”
Section: Methodsmentioning
confidence: 99%
“…Microdialysis is a catheter-based method for continuous sampling of the free unbound and active fraction of antibiotics in the interstitial space of the tissue of interest [43][44][45].…”
Section: Microdialysismentioning
confidence: 99%